MODEL BANGKITAN PERGERAKAN RUMAH TANGGA BAGI PENGGUNA SEPEDA MOTOR BERDASARKAN LOKASI TUJUAN PERJALANAN DI KOTA BANDA ACEH - Raina Permitalia Dinda; Renni Anggraini; Sugiarto Sugiarto (Prodi Magister Teknik Sipil Unsyiah, 2018)
Population growth in banda Aceh city is increasing every year resulting in increased community movement. Community movement in Banda Aceh city dominated by motorcycle users, there are several factors that influence the Trip generation of Household in Banda Aceh city. One of which is the characteristic of trip behaviour which is the location of the choosen destination of the community. This research aims to know the variables of socio-economic characteristics, demography, and trip behavior in 4 sub-districts that are jaya Baru sub-dsitrict, banda raya, Lueng bata, and Kuta raja sub-dsitrict in Banda Aceh city, obtained trip generation model of motorcycle users on the household base don selection of destination location travel, what factors that affect the trip generation and analyzing the probability and error rate from the selection of each generation. This method is done by using home interview survey method. Sampling of household population to be studied by using stratified random sampling method. Method use to obtained model and probability also the relationship of variables that influenced in this research is by binomial logistic regression analysis model then processed with the help of SPSS v20 software program. From this research obtained 2 models which are the trip generation model based on destination location of trip to other places with the most influential variables are job status and last education. The generation probability is ≤ 3 movements of 77% and generation probability greater than 3 with movement of 23%. The second model is the trip generation model is based on the destination location of trip to office/school with the most influential variables are number of family members who attened school and number of family members, the probability of trip generation is. ≤ 5 movements of 81% and probability of trip generation greater than 5 movements of 19%. Both of two models also meets the specifications error value which si below 10%..